Cover Picture: Stable Isolated Metal Atoms as Active Sites for Photocatalytic Hydrogen Evolution (Chem. Eur. J. 8/2014). Issue 8 (17th February 2014) - Xing, Jun; Chen, Jian Fu; Li, Yu Hang; Yuan, Wen Tao; Zhou, Ying; Zheng, Li Rong; Wang, Hai Feng; Hu, P.; Wang, Yun; Zhao, Hui Jun; Wang, Yong; Yang, Hua Gui
<x xml:space="preserve">Abstract</x> TiO2 photocatalysts loaded with isolated Pt atoms were successfully synthesized by a simple and convenient technique as described by H. F. Wang and H. G. Yang et al. in their Communication on page 2138 ff. Isolated Pt atoms can stably anchor on TiO2 and exhibit a high photocatalytic hydrogen evolution performance compared with Pt nanoparticles or clusters. Moreover, the configurations of the isolated Pt atoms and their catalytic hydrogen evolution activity were calculated by large‐scale periodic DFT analysis. The results obtained for such model catalysts not only opens a door for synthesizing high‐efficiency catalytic materials, but also has a great potential to reduce the high cost of commercial noble metal catalysts in industry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>